The Effectiveness of Soy Bean, Oxcytocin Massage and Back Massage on Breast Milk Production of Postpartum Mothers Systematic Literature Review - Handayani Handayani; Masrifan Djamil; Sri Wahyuni; Shandy Wigya M (Publikasi Indonesia, 2022)
Breast milk production that is less or not smooth is a problem that is often experienced by postpartum mothers. That is due to lack of nutritional intake and lack of therapy to facilitate milk production. Giving soybeans, oxytocin massage and back massage are ways to increase breast milk production. The search for articles in this systematic literature review uses 6 databases with a time start from 2015-2020. The articles using Indonesian and English. The inclusion criteria were postpartum mothers, the interventions given were using soybean, oxytocin massage, and back massage. The measurement results are in the form of breast milk production. The designs used in the article search are True Experiment and Quasy Experiment. The preparation of this systematic literature review uses the PRISMA guideline. Analysis of data from a systematic literature review, 17 studies were eligible for identification, 6 studies were true experiments and 11 studies were quasy experiments. The intervention soybean containing isoflavone showed statistically significant results on breastmilk production with p value < 0.05. The intervention oxytocin massage showed significant results on breastmilk production with p value <0.05. Intervention back massage showed significant results on breastmilk production with p value <0.05. intervention OKPU massage showed significant results on breastmilk production with p value <0.05. Interventions with soy, oxytocin massage, back massage and OKPU massage have a positive effect on breastmilk production. Oxytocin massage and OKPU massage proved more effective based on significance value and effect size.